Proposta para estruturação da gestão da melhoria contínua em uma fabricante de bebidas - Zampini, Carla Simão (2008)
Due to fast changes in the economic, market, and technological environment, there is a demand of new management models aiming to improve products, processes, services and management systems in order to make business performance sustainable and provides a platform of growth. Therefore, companies have been implementing activities, formal or informal, structured or not, which in some way it results into an improvement, a progress of large-scale action, consequently, competitive advantages in a long term. The aim of this study is to propose the development of a continuous improvement structure to a Brazilian beverage manufacturer. Continuous improvement practices, in this company, are traditionally implemented in a non articulated way according to its business goals, and are informally done. Consequently, it is not sustainable in a long term. This associated with the concept that doesn t exist a final model to implement, because each models need to be adopted according to the company s characteristics was the reason to develop a propose of continuous improvement structure. This study was based on action research method because it tries to bring a proposal based on real problems and a wide search for solutions, through the interaction of researchers and the company members. Literature review helped us to identify some models to manage continuous improvement activities, but every company has to identify the most suitable model according to its needs and specifications. Literature review and diagnosis done by the company, through action research method, allowed a formulation of the organizational problem and the development of a continuous improvement management structure according to the company s strategic goals and needs. We could also give some guide in order to initiate the proposal. This proposal briefly includes four key elements: - Formalization of Continuous Improvement (CI) process: - Alignment to the company strategies; - To bring a good environment and motivation to CI and; - Development of Capacity to CI. All of them together permit an integration of the continuous improvement activities and the alignment to the strategic goals of the company. Recommended activities, in order to have the beginning of the proposal, are the adjustment of the responsibilities and the review of processes and activities that already exist in the company in order to integrate the continuous improvement activities management, supporting the organization learning and management system.